TUGAS KORDINASI BHABINKANTIBMAS DALAM PENGAWASAN PENGGUNAAN DANA DESA - Mustakim, Mustakim; Kasmar, Kasmar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Supervision of Bhabinkamtibmas in the use of village funds, aims to ensure that Bhabinkamtibmas can carry out their duties properly. The method used is a normative legal research method with a statutory and conceptual approach. The results of this study indicate that the supervision of Bhabinkamtibmas in the use of village funds is needed to increase the role of Bhabinkamtibmas in village development and coordinate with village community leaders. Because when many community leaders supervise, it is better for the Village Government not to abuse their positions and KKN in the implementation of village development because village funds can tempt officials to do wrong. Bhabinkamtibmas should be involved since planning or deliberation in the hamlet/village, village deliberations (musrenbangdes) so that the development direction is according to priorities in the village and monitoring the village development process. Thus the task of supervising Bhabinkamtibmas can run smoothly, so that it can build a prosperous village without corruption, collusion and nepotism.